2014
DOI: 10.5455/jice.20140826110059
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tapinanthus globiferus and Zanthoxylum zanthoxyloides extracts on human leukocytes in vitro

Abstract: Objective:This study aimed at investigating the genotoxicity and cytotoxicity effect of Tapinanthus globiferus and Zanthoxylum zanthoxyloides to human leukocytes. In addition, the reductive potential and the chemical composition of the two plant extracts were also determined.Materials and Methods:Human leukocytes were obtained from healthy volunteer donors. The genotoxicity and cytotoxicity of T. globiferus and Z. zanthoxyloides were assessed using the comet assay and trypan blue exclusion, respectively. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…The reduction of the ferric ion to ferrous ion increased with increase in the concentration of the extract (Table 2) which agrees with the studies carried out [20]. Natural antioxidants possess the ability to reduce Ferric (Fe 3+ ) ion to ferrous (Fe 2+ ) ions.…”
Section: Discussionsupporting
confidence: 88%
“…The reduction of the ferric ion to ferrous ion increased with increase in the concentration of the extract (Table 2) which agrees with the studies carried out [20]. Natural antioxidants possess the ability to reduce Ferric (Fe 3+ ) ion to ferrous (Fe 2+ ) ions.…”
Section: Discussionsupporting
confidence: 88%
“…This assertion is buttressed by the works of Nguegium et al and Ogunbolude et al which showed that AME and TGE are rich in bioactive phytochemicals which are known to have several health benefits including the management of diabetes and other metabolic diseases. 18,22…”
Section: Resultsmentioning
confidence: 99%
“…Z. zanthoxyloides Lam. also has an action on hematological parameters and oxidation (Ogunbolude et al, 2014;Ikumawoyi et al, 2016). Decoction is the most commonly used method of preparation and is obtained by boiling plants in water.…”
Section: Discussionmentioning
confidence: 99%